OPTIMALISASI KINERJA TIM MEDIA SOSIAL MELALUI KEPEMIMPINAN YANG EFEKTIF DALAM MENINGKATKAN CITRA MEREK UMKM BAKSO BERANAK MAS GAYENG - Hannah Naila Indie Fadhillah; Riska Rosdiana; Tarisa Alrini Sabadhillah; Nabila Khoirotunnisah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
The development of digitalization has created new opportunities in marketing, particularly for Micro, Small, and Medium Enterprises (MSMEs). However, many MSMEs still struggle to manage social media effectively due to limitations in time, digital literacy, and unstructured teams. This study aims to examine how effective leadership can optimize the performance of social media teams in enhancing brand image and directly increasing sales of the MSME Bakso Beranak Mas Gayeng, particularly on Instagram and TikTok platforms. The author is directly involved as the team leader, responsible for task delegation, content planning, and performance evaluation using the System Development Life Cycle (SDLC) approach. The project results show a significant increase in brand awareness, audience engagement, market reach, and the MSME’s brand image through social media, supported by effective leadership in optimizing team performance.